The chemical characterisation of authigenic carbonates from the Witbank no. 2 coal seam : environmental and diagenetic implications - Van der Spuy, David (Department of Geological Sciences, 2016)
Six different types of authigenic carbonate were identified associated with the no.2 coal seam in the Witbank basin. These are: l) cell-filling carbonate, 2) early formed spberulites, 3) massive carbonates, 4) cleat-filling carbonate, 5) fracture-filling carbonates and 6) carbonate cement of associated sands. The textural relationships, depth of burial and chemical evolution of these carbonates were studied with the aid of X-ray diffraction, total organic carbon analysis, vitrinite reflectance, reflected and transmitted light microscopy, scanning electron microscopy and electron microprobe analysis. Comparison with the studies of Matsumoto and Iijima (1981), Curtis and Coleman (1986) and other literature showed the Witbank carbonates to have followed a fairly complex path in terms of chemical evolution. The chemistry of the earliest cell-filling carbonates is indicative of an early brackish, alkaline environment with high sulphate levels, with occasional local oxidising conditions prevailing during precipitation. Spherulite chemistry is largely representative of the continuation of alkaline conditions with high sulphate supply. Those forming closer to palaeohighs are sideritic and possibly reflect the input of fresher run-off water, allowing more acidic conditions locally. Compositional zonation of some examples indicates initial acidic conditions and later alkaline conditions. Massive carbonates are considered to have formed, at least in some cases, from amalgamations of these earlier spherulites. They are high-Ca carbonates, siderite or dolomite. A number of the high-Ca massive carbonates were found to be aragonite. These are considered to have precipitated from water with high ionic strength, in the presence of humic acids. The chemistries of these massive carbonates are representative of the continuation of relatively, alkaline conditions, or, in some cases, represent a strong brackish or marine imprint over the earlier fresh water chemistries. Chemical trends and isotope data suggest continued formation with burial. Later formed carbonates filling cleats and fractures show more diverse compositions and are interpreted as the results of mixing of pore waters at depth, primary silicate dissolution and later percolation of groundwaters after uplift. The overall evolution of the authigenic carbonates in the Witbank no.2 seam leads to the interpretation that the early swamp was only locally "fresh", and provides strong evidence for a marine influence at both early and late stages of deposition and diagenesis.